The factors contributing to the rise of religious extremism in Malaysia - Akhmetova, Elmira; Aminudin, Rabi'ah (2019)
This paper examines the factors for the rise of religious extremism in Malaysia by highlighting the problems arose from the politicization of Islam in Malaysia, economic conditions, and the impact of colonialism.